2014
DOI: 10.1002/anie.201402229
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Intermolecular α‐Arylation of Amides

Abstract: A new approach for the fully chemoselective α-arylation of amides is presented. By means of electrophilic amide activation, aryl groups can be regioselectively introduced α- to amides, even in the presence of esters and alkyl ketones. Mechanistic studies reveal key reaction intermediates and emphasize a remarkably subtle base effect in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(67 citation statements)
references
References 91 publications
2
60
0
5
Order By: Relevance
“…Recently, we34353637383940 and others41424344454647484950515253545556 reported the metal-free, sulfoxide directed57 C–H functionalization of a variety of molecular scaffolds, which was enabled by an interrupted Pummerer reaction28. Spurred on by these recent achievements, we considered the use of benzothiophene S -oxides 1 for the synthesis of important C3-functionalized benzothiophenes, as the corresponding sulfonium salts I and II , formed after reaction with the coupling partners, lack aromaticity about the five-membered ring and should therefore undergo facile C–C bond formation via [3,3]-sigmatropic rearrangement58, thus delivering unexplored reactivity not accessible in benzothiophenes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we34353637383940 and others41424344454647484950515253545556 reported the metal-free, sulfoxide directed57 C–H functionalization of a variety of molecular scaffolds, which was enabled by an interrupted Pummerer reaction28. Spurred on by these recent achievements, we considered the use of benzothiophene S -oxides 1 for the synthesis of important C3-functionalized benzothiophenes, as the corresponding sulfonium salts I and II , formed after reaction with the coupling partners, lack aromaticity about the five-membered ring and should therefore undergo facile C–C bond formation via [3,3]-sigmatropic rearrangement58, thus delivering unexplored reactivity not accessible in benzothiophenes.…”
Section: Resultsmentioning
confidence: 99%
“…Given our ongoing interest in metal-free a-arylation of bketo esters [11] and amides, [12] we sought to develop chiralitytransfer strategies.H owever,i ni nitial efforts (Scheme 1B), the use of chiral sulfoxide 6afor the arylation of b-ketoester 5 met with failure,s ince only racemic product 7 was obtained despite several attempts. [13] We ascribe this disappointing result to configurational instability of the sulfur center during the reaction.…”
mentioning
confidence: 99%
“…Maulide and co-workers showed that aryl sulfoxides 53 can undergo ortho CÀHa lkylation upon treatment with activated amides (Scheme 35). [53] Thea mides were activated with triflic anhydride in the presence of 2-iodopyridine and formed iminium dications 88 via iminium triflates.E ither iminium dication 88 or keteniminium triflate 89 reacts with the nucleophilic sulfoxide oxygen atom to form sulfonium salt 90,w hich can undergo a [ 3,3]-sigmatropic rearrangement. This CÀH/CÀHcoupling reaction has abroad scope and even allows for the coupling of hindered amides and, impressively, the selective a-arylation of amides in the presence of esters and ketones.…”
Section: Reactions Of Sulfoxides With Electrophilic Coupling Partnersmentioning
confidence: 99%